Building a strong european alliance for personality disorder research and intervention - Mehlum, Lars; Bateman, Anthony; Doering, Stephan; Bohus, Martin (BioMed Central, 2018)
People with personality disorders frequently face stigma, ignorance and pessimism regarding the treatability of their disorders. This is despite substantial progress that has been made in developing a number of effective evidence based psychotherapeutic treatments. However, expertise in how to systematically deliver these treatments in a sustainable way throughout Europe is largely lacking. To bridge the gap between evidence based treatments and their implementation in health services, the European Society for the Study of Personality Disorders is currently building a new alliance of experts to promote personality disorder scholarship, and to support the development of clinical expertise and systematic treatment implementation throughout Europe. The aim of this paper is to describe how the Society is currently using its interdisciplinary and international roster of experts to address the specific treatment and research needs of the European personality disorder field, particularly to countries in which expertise in the field is less developed.
Aus: Borderline Personality Disorder and Emotion Dysregulation, 5 (2018), Nr. 7. pp. 1-5. ISSN 2051-6673